2022
DOI: 10.1111/jgs.17794
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of coronary revascularization strategies in older adults presenting with acute coronary syndromes

Abstract: Background The optimal coronary revascularization strategy to maximize the patient‐centered outcome of days alive and out of hospital (DAOH), in multimorbid older (≥65‐years) adults after an acute coronary syndrome (ACS) is incompletely understood. Methods Using Kaiser Permanente Northern California Health Plan databases, we identified 3871 patients ≥65‐years presenting with ACS between 1/1/2010–3/1/2018 who underwent coronary revascularization with either coronary artery bypass grafting (CABG, N = 1575) or mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Epidemiology studies have showed older age was cardiovascular disease (CVD) risk factor,especially for CAD [14]. One the one hand, with the increase of age, there were genomic instability cellular senescence and epigenetic changes in molecular hallmarks [15]. On the other hand, the comorbidities, such as hypertension, diabetes, may also predispose elderly patients to an increased risk of the development and process of atherosclerotic plaques [16].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiology studies have showed older age was cardiovascular disease (CVD) risk factor,especially for CAD [14]. One the one hand, with the increase of age, there were genomic instability cellular senescence and epigenetic changes in molecular hallmarks [15]. On the other hand, the comorbidities, such as hypertension, diabetes, may also predispose elderly patients to an increased risk of the development and process of atherosclerotic plaques [16].…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing large studies will attempt to elucidate this crucial aspect [29,30]. Finally, in a selected group of patients (those with a low burden of comorbidities and no frail) presenting with ACS and having multivessel and/or left main coronary artery disease (CAD), coronary artery bypass grafting should be considered if percutaneous treatment is not feasible [31,32]. In any case, in all older patients with ACS undergoing invasive management (coronary angiogram ± PCI), certain precautions should be considered due to their higher likelihood and greater impact of developing adverse events.…”
Section: Revascularization Approachmentioning
confidence: 99%
“…Recent studies comparing the percutaneous approach with surgical treatment of CAD brought mixed results. The superiority of CABG was especially marked in patients with MVD, but not in LMCAD [ 63 , 64 , 65 ]. A substudy from the DELTA registry (Drug-Eluting stent for LefT main Artery) found no difference in the occurrence of the primary endpoint in octogenarians after CABG and PCI [ 66 ].…”
Section: Evidence Supporting Lmca Revascularizationmentioning
confidence: 99%